The Sensitivity and Specificity of Measuring the Thickness of Myometrium to Predict the Time of Spontaneous Labour in Preterm Prelabor Rupture of Membranes and Oligohydramnios - Luma Zeiny (مجلة الكوفة الطبية)
Background: Preterm prelabour rupture of membranes (PPROM) accounts for one- third of cases of preterm labour which is the leading cause of perinatal morbidity and mortality. The time from the rupture of membranes until labour, i.e. the latent period (LP), is an important factor in neonatal outcome.  Aim of the study: The present study aims to determine the sensitivity and specificity of measuring the thickness of myometrium for the prediction of LP. Patients and methods: This cross-sectional observational study was performed in Az-Zahraa Teaching Hospital in Najaf-Iraq during the period from the first of August 2016 to the first of October 2017. A total of 89 patients who admitted with the diagnosis of PPROM at the 26th to the 34th weeks of gestation with oligohydramnios were included in the study. The thickness of myometrium was measured via transabdominal ultrasound in the lower uterine segment (LSMT), anterior (AMT), posterior (PMT) and fundal (FMT) parts of uterus within 24 hours of membranes rupture. Results: The mean measurements of LSMT, AMT, PMT and FMT in patients with PPROM and oligohydramnios were 7.25±2.31, 7.87±3.45, 8.71±3.88 and 8.65±3.72 respectively. The sensitivity and specificity of measuring AMT for prediction of LP > 7 days were 80% and 53%; those for PFT were 80% and 34.1% respectively at a cut-off point of 6.5 mm while the FMT was found to be 60% sensitive and 34.1% specific. LSMT was 80% sensitive and 43.9% specific for recognition of LP > 7 days at a cut-off point of 7.5mm. Conclusions: measurement of the thickness of the myometrium may be a sensitive but non-specific tool for the prediction of the latent period.